Attempt of Experimental Transmission of Hydatid Infection from Human to Dogs: Amall Hassen Atia* Azhar Ali Faraj** Abdullah L AL-Mammry* - Atia, Amall Hassen (The Iraqi Journal of Veterinary Medicine, 2011)
An experimental infection of 3 dogs with protoscoleces of human origin were carried out Hydatid cyst was surgical removed from 26 years old female. On autopsy all dogs were found not harbor any Echinococcus granulosus worms Infection with the metacestode stage in unusual intermediate hosts failure for procreation which do not play a role in the transmission cycle in Iraq. In conclusions: the reason could be related between the host and chemical composition of hydatid fluid failure of induces infection